Protocol for RYMV Inoculation and Resistance Evaluation in Rice Seedlings - Pinel Galzi, A.; Hébrard, E.; Traoré, O.; Silué, D.; Albar, L. (Bio-Protocol, LLC, 2018)
Rice yellow mottle virus (RYMV), a mechanically transmitted virus that causes serious damage to cultivated rice plants, is endemic to Africa. Varietal selection for resistance is considered to be the most effective and sustainable management strategy. Standardized resistance evaluation procedures are required for the identification and characterization of resistance sources. This paper describes a protocol for mechanical inoculation of rice seedlings with RYMV and two methods of resistance evaluation – one based on a symptom severity index and the other on virus detection through double antibody sandwich-enzyme linked immunosorbent assay (DAS-ELISA).